A Self‐Regulated Electrostatic Shielding Layer toward Dendrite‐Free Zn Batteries. Issue 37 (15th August 2022) - Hu, Zhengqiang; Zhang, Fengling; Zhao, Yi; Wang, Huirong; Huang, Yongxin; Wu, Feng; Chen, Renjie; Li, Li
Abstract: Although aqueous Zn batteries have become a more sustainable alternative to lithium‐ion batteries owing to their intrinsic security, their practical applications are limited by dendrite formation and hydrogen reactions. The first application of a rare earth metal type addition to Zn batteries, cerium chloride (CeCl3 ), as an effective, low‐cost, and green electrolyte additive that facilitates the formation of a dynamic electrostatic shielding layer around the Zn protuberance to induce uniform Zn deposition is presented. After introducing CeCl3 additives, the electrochemical characterizations, in situ optical microscopy observation, in situ differential electrochemical mass spectrometry, along with density functional theory calculations, and finite element method simulations reveal resisted Zn dendritic growth and enhanced electrolyte stability. As a result, the Zn–Zn cells using the CeCl3 additive exhibit a long cycling stability of 2600 h at 2 mA cm −2, an impressive cumulative areal capacity of 3.6 Ah cm −2 at 40 mA cm −2, and a high Coulombic efficiency of ≈99.7%. The fact that the Zn–LiFePO4 cells with proposed electrolyte retain capacity significantly better than the additive‐free case is even more exciting. Abstract : Building stable electrolytes is very crucial for constructing stable Zn batteries as hydrogen reaction and the dendritic growth of Zn‐metal anodes. Here, a rare metal salts additive (CeCl3 ) is employed to stabilize the electrolyte in Zn batteries via the formation of a self‐regulated electrostatic shielding layer. The rare metal salts additive strategy affords emerging chances for rational electrolyte design for stable Zn batteries.